1995
DOI: 10.1016/s0886-3350(13)80474-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of central islands after excimer laser refractive surgery

Abstract: We conducted a study to determine the prevalence of central islands after refractive excimer laser surgery and the factors associated with their occurrence. A VISX Twenty/Twenty excimer laser was used to perform 157 photorefractive keratectomy (PRK) and 263 photorefractive astigmatic keratectomy (PARK) procedures. Corneal topography was assessed in 156 patients three months postoperatively using a topographic analysis system. Central islands were seen in 67% of patients; 26% had islands of 3.0 diopters (D) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…We have termed these areas corneal traumatic 'topographic lagoons', adhering to the developing 'geographic' nomenclature of corneal topographic features such as the previously described excimer laser related 'central topographic islands'. 16 While in a control group of 135 eyes only two corneas (1.5%) exhibited this topographic feature, two of the 11 patients retrospectively analysed, and one of 11 patients prospectively analysed following epithelial trauma exhibited this abnormality. It might therefore be reasonably concluded that these focal abnormalities, in patients who have not recently been wearing contact lenses or have pre-existing corneal disease, represent focal changes in the healing cornea which are associated with decreased dioptric power.…”
Section: Groupmentioning
confidence: 90%
See 1 more Smart Citation
“…We have termed these areas corneal traumatic 'topographic lagoons', adhering to the developing 'geographic' nomenclature of corneal topographic features such as the previously described excimer laser related 'central topographic islands'. 16 While in a control group of 135 eyes only two corneas (1.5%) exhibited this topographic feature, two of the 11 patients retrospectively analysed, and one of 11 patients prospectively analysed following epithelial trauma exhibited this abnormality. It might therefore be reasonably concluded that these focal abnormalities, in patients who have not recently been wearing contact lenses or have pre-existing corneal disease, represent focal changes in the healing cornea which are associated with decreased dioptric power.…”
Section: Groupmentioning
confidence: 90%
“…Theoretically, focal changes in the corneal epithelium may contribute more than one dioptre of corneal opment of central topographic islands after photorefractive keratectomy. 16 However, it is also entirely possible that the affected epithelium may give rise to focal areas of abnormal wetting which may cause repeatable, but artefactual, areas of apparently reduced dioptric power on corneal topographic analysis.…”
Section: Groupmentioning
confidence: 99%
“…For the 89 high myopes with 1-year follow-up, the mean SEQ was -.80 (± 1.06). The mean SEQ at 1 year for the 15 Mean SEQ in high (n=194) and extreme (n=53) myopes undergoing excimer laser surgery. Plot of preoperative and 6-month SEQ in high (n=194) and extreme (n=53) myopes undergoing excimer laser surgery.…”
Section: Methodsmentioning
confidence: 99%
“…They used a full laser beam with internal masks or diaphragms for customized ablations, but the ablation plume sometimes resulted in untreated areas, so‐called central islands (Lin ; Levin et al. ). Scanning‐slit lasers used a smaller slit‐shaped laser beam capable of rotation and were able to treat larger‐diameter ablation zones.…”
Section: Introductionmentioning
confidence: 99%